2022
DOI: 10.1111/dth.15476
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab therapy in atopic dermatitis is safe during COVID‐19 infection era: A systematic review and meta‐analysis of 1611 patients

Abstract: The aim of this meta‐analysis is to evaluate the safety of dupilumab use in the management of atopic dermatitis (AD) during the current pandemic regarding the risk and the hazards of COVID‐19 infection. Seven databases (Google Scholar, Web of Science, Scopus, Virtual Health Library, PubMed, System for Information on Gray Literature in Europe, and The New York Academy of Medicine) were searched for eligible studies from inception until November 24, 2021. The quality of evidence was rated using the National Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…A survey revealed that the majority of the AD patients experienced AD flares with mild worsening of the disease during the COVID‐19 pandemic 197 . Dupilumab seems to be safe and crucial for a better outcome of COVID‐19 and should be continued in AD patients during the COVID‐19 pandemic 198 . During COVID‐19, AIT was initiated and continued by most physicians in patients without indications of SARS‐CoV‐2 infection 199 .…”
Section: Management Of Allergic Diseases During the Covid‐19 Pandemicmentioning
confidence: 99%
“…A survey revealed that the majority of the AD patients experienced AD flares with mild worsening of the disease during the COVID‐19 pandemic 197 . Dupilumab seems to be safe and crucial for a better outcome of COVID‐19 and should be continued in AD patients during the COVID‐19 pandemic 198 . During COVID‐19, AIT was initiated and continued by most physicians in patients without indications of SARS‐CoV‐2 infection 199 .…”
Section: Management Of Allergic Diseases During the Covid‐19 Pandemicmentioning
confidence: 99%
“…Further confirmation of the antiviral potential of photochemotherapy comes from the finding of photoinactivation potential in plasma with Amotosalen and 3 J/cm 2 of UVA light of six RNA-enveloped viruses, including SARS CoV [ 57 ]. Beyond the newly explored therapeutic potential, the promising role of phototherapy is also related to its choice as a viable therapeutic alternative to immunomodulating/immunosuppressive drugs used in AD and similar conditions whose use should be limited because of their ability to impact vaccine-induced immune responses [ 58 , 59 , 60 , 61 ] and for their suppressive action on intrinsic antiviral immunity [ 62 , 63 , 64 ] except for dupilumab, whose evidence of use in the pandemic era is reassuring [ 65 , 66 , 67 ].…”
Section: Atopic Dermatitis Treatmentmentioning
confidence: 99%
“…A survey revealed that the majority of the AD patients experienced AD flares with mild worsening of the disease during the COVID-19 pandemic 168 . Dupilumab seems to be safe and crucial for a better outcome of COVID-19 and should be continued in AD patients during the COVID-19 pandemic 169 .…”
Section: Management Of Allergic Diseases During the Covid-19 Pandemicmentioning
confidence: 99%